Malignant Hyperthermia and Idiopathic HyperCKemia - Pashtoon Murtaza Kasi (Case Reports in Medicine)
Malignant hyperthermia (MH) is a rare but life-threatening condition that is more frequently encountered and discussed within the anesthesia literature. Here we through a case specifically discuss the susceptibility of individuals and/or families with asymptomatic unexplained elevations of creatine kinase (CK), also frequently referred to as hyperCKemia or idiopathic hyperCKemia (IHCK) in recent reports. The clinical implications would be to underscore the importance of this as a susceptibility to developing MH and highlight the importance of genetic susceptibility testing in such cases. Anesthesiologists and critical care intensivists as well as primary care physicians should keep this in mind when seeing patients with asymptomatic hyperCKemia and potentially inform them about the possibility of developing MH if exposed to triggering agents. Genetic susceptibility testing should be considered if available and family members should also receive nontriggering agents when undergoing anesthesia and wear Medic Alert tags.